Spinibdella Thor (Acari: Bdellidae) from southern Africa: descriptions of five new species and the redescription of S. thori (Meyer & Ryke) - Omukunda, Elizabeth; Theron, Pieter D; Ueckermann, E A (Zootaxa, 2012)
Five new species of Spinibdella are described and figured: S. ankylotricha sp. nov., S. polyattenuata sp. nov., S. pongolensissp. nov., S. namibiensis sp. nov., and S. trinomma sp. nov. Where available, immature stages are also described. Spinibdellathori (Meyer & Ryke) is redescribed and S. cronini (Baker & Balock) is reported for the first time from southern Africa. Keys to the genera of Bdellidae and South African Spinibdella are given.